البنيــة الحجاجية في الخطـاب النثـري الأدبـي رسائـل هارون الرشيـد أنموذجــا - ربعاني, وردة (جامعة الوادي - University of Eloued, 2022)
يحتل الحجاج جانبا مهما في المسار اللساني التداولي ؛وهو من الأعمال التي تقوم على الإبداع والجمال، وميزة من مميزات الخطاب. وقد أصبح في العقود الأخيرة محل الدارسين واللغويين، وذلك من خلال الأبحاث الكثيرة التي قامت بخصوصه وانفتاحه، وتنوع مجالاته، فنجده في النصوص القرآنية والخطابات الأدبية كالشعر والخطب والرسائل الديوانية والإخوانية. ومن النصوص التي يجنح صاحبها بشكل ملحوظ إلى إحضار ما استطاع من الأدلة والبراهين والحجج النص النثري الأدبي أو الرسالة بنوعيها ولذلك ارتأينا أن نتلمس أهم الحجج التي ورد فيها، واخترنا لذلك بعض رسائل هارون الرشيد أنموذجا للإجابة عن الإشكالية التالية: كيف برز الحجاج في رسائل هارون الرشيد؟ وما هي أنواعه؟ وما النوع الأكثر هيمنة على خطابه الرسائلي؟ Argumentation occupies a significant part in the deliberative linguistic track. It is, among others, one work based on creativity and beauty, and is as well one of the discourse features. It becomes a subject of interest to scholars and linguists during the last decades, due to numerous researches dealing with its essence, openness and fields’ diversity. We find argumentation in Quranic texts and literary discourses such as poetry, speeches and letters whether they were Diwaniya or Ekhwanya. One of the texts that remarkably requires all kinds of evidence, proof and arguments is the literary prose text or the letter including its both types. Therefore, we decided to consider the most eminent mentioned arguments within them, then we chose some letters of Harun al-Rachid as a model for the purpose of answering this problematic: How did argumentation stand out in Harun al-Rachid’s letters? What types did it include? And what was the dominant type within his letters discourse?
The Argumentative Structure In The Literary Prose Discourse Harun Al-rachid’s Letters As A Model.
مقال
Keywords: البنية الحجاجية ; المرسل ; المتلقي ; الإقناع ; البراهين ; الرسائلي; Argumentative structure ; sender ; receiver ; persuasion ; proofs ; mechanisms